TERAPI SUARA DALAM MENURUNKAN TINGKAT STRES PADA MAHASISWA - Nurul Qomaria Usman (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2020)
AbstractStress is the pressure experienced by a person, whether caused by internal or external pressure, which is characterized by physiological, cognitive changes as well as fairy stress, which is generally negative and destructive in nature. This research was conducted with the aim of knowing the effect of sound therapy in reducing stress levels experienced by students of UIN Sunan Kaliga Yogyakarta. The form of sound therapy given in this study uses the reading of Yasiin's letter to the research subject. This research method uses experimental research in the form of a pretest-posttest control design. The population in this study were students of UIN Sunan Kalijaga Yogyakarta. Sampling using purposive sampling technique with a sample of 14 people divided into the experimental class and the control class. The treatment was given once for each group. The research instrument was a stress level measurement using DASS 42. The data analysis used was the Wilcoxon test and the Mann Whitney U test with a significant level of 0.05. The Wilcoxon test results show that the P or Pv value is 0.038. While the significant level (α) of the research is 0.05. So that the value of P <α or 0.038 <0.05, which means that there is an effect of sound therapy listening to Yasiin's letter on reducing stress levels in UIN Sunan Kalijaga students. The results of the Mann Whitney U test show that the P value is 0.153> 0.05, which means that there is no significant difference between the experimental group and the control group. There is an effect of voice therapy listening to Yasiin's letter in reducing stress levels, but there is no change in the stress level category, namely the subject remains in the severe stress category.